RETURN PASAR MODAL DAN PASAR RAKYAT? - M Ali Fikri; Saipul Arni Muhsyaf; Nungki Kartikasari (Jurnal Aplikasi Akuntansi, 2021)
The value relevance according to Beaver (1968) is the explanatory power of accounting information, for example accounting earnings and book value are related to firm value represented by stock prices. The phenomenon is that many players from the capital market are carried out by the middle to upper class, even though on the other hand there are small investments that also generate returns, for example the traditional market. This study examines the differences in the value relevance of the capital market and the traditional market to obtain empirical evidence about the relevance of the value of stock returns between the capital market and the traditional market. This research was conducted around the scope of the Indonesian Capital Market (IDX) and Traditional Markets in the Mataram area. The results showed that the value of traditional market returns was more profitable than the capital market.